ANALISIS HASIL TANGKAPAN RAJUNGAN (PORTUNUS PELAGICUS) DENGAN ALAT TANGKAP BUBU LIPAT DI DESA WARUDUWUR KECAMATAN MUNDU KABUPATEN CIREBON JAWA BARAT - Dirja, Dirja (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2019)
Folding bubble is one of simple fishing gear typesthat is used to catch the crab (Portunus pelagicus)by traditional fishermen for a long time. Folding fishing gear is widely used by fishermen, especially in Waruduwur Village, Mundu Subdistrict, Cirebon District. The choice of using folding fishing gear, because in addition to the relatively cheap price, materials and tools easy to can and easy operation. Besides, the fishing gear is environmentally friendly because it is selective towards the catch. The purpose of this research is to analyze the catch of small crabs in the folding fishing gear and to know the method of catching bubu fold in Waruduwur Village, Mundu Subdistrict, Cirebon Regency. This research use case study, as case unit is the business activity of the bubu fishing unit in the village Waruduwur District Mundu Cirebon District. Data analysis using financial analysis include profit / loss analysis, Revenue Cost Ratio (R / C), Payback Period (PP) Analysis, Break Event Point Analysis (BEP), while for analysis of investment criteria using Return Of Infestment Analysis (ROI). The results showed that the operation of fishing gear for four months (April-July) in 16 trips obtained the total composition of the main catches as much as 61,700 kg and the composition of 332 kg byproducts. The main catches in May were 79 kg (40.10%), May (78.05%) in May, 73 kg (50.34%) in June and 55kg (52.38%) in July, , While the by-catch is made up of crabs, fish, cuttlefish, and snails. Methods of operation of fishing gear include preparation, decrease of catching equipment (setting), soaking, and hauling.